Novel solid-state synthesis of halide free alane - Knight, D.; Dinh, L.; Paskevicius, M.; Buckley, Craig; Zidan, R. (AMER CHEMICAL SOC, 2012)
The traditional aluminum hydride (alane, AlH3) synthesis involves reacting AlCl3 and LiAlH4 in diethyl ether, resulting in the formation of the alane etherate adduct, AlH3·h[(C2H5)2O]. The desired crystallized, stable a-AlH3 can only be obtained by either extensive vacuum distillation and heating of the etherate or by a crystallization process involving a large, heated bath of a benzene/toluene solution. These processes tend to be costly due to the several hours of vacuum pumping and/or heating required as well as dangerously using large amounts of flamable, toxic solvents. It is demonstrated here that a-AlH3 can be obtained by simply mixing AlCl3 and LiAlH4 in the solid state and slowly heating to 75° C. The a-AlH3 product can be washed with minimal solvents to remove the LiCl bi-product, leading to zero formation of any alane adducted materials. Although simple mixing and heating the reactants can provide a 40% yield of alane, the application of moderate pressure while heating increases this yield to over 60 % of cvrystalline a-AlH3.